Fast neutron fluence estimation by measurement of 93mNb and 93Mo - Ichikawa Masashi; Tanaka Shigeaki; Chatani Kazuhiro (EPJ Web of Conferences, 2023)
The possibility for estimation of fast neutron fluence from 93mNb produced from Nb contained in structural component materials of nuclear power plants was investigated as an evaluation tool for extending plant operating lifetime. First, to establish a measurement method for 93mNb in structural component materials, chemical separations and measurements of 93mNb were carried out using specimens of fast neutron-irradiated XM-19 and X-750 alloy; these are used as structural component materials and contain Nb as a component. The 93mNb activities obtained from the measurements of both XM-19 and X-750 alloy agreed well with the calculated values of 93mNb, which were simply calculated from the evaluated fast neutron fluence. On the other hand, in the case of type 316L stainless steel, which contains Mo, Mo derived 93mNb presents a problem, so an approach was used that estimates the amount of Mo derived 93mNb based on 93Mo measurements with the third specimen, neutron-irradiated type 316L stainless steel. The difference between the measured and calculated 93mNb values was about two-fold, indicating that the estimation method for 93mNb produced from Mo needs to be improved.